REVITALISASI WEBSITE DI PERPUSTAKAAN DAN KEARSIPAN KOTA LANGSA DENGAN DESAIN UI/UX - Siregar, Ginda Maruli Andi; Hasibuan, Ade Zulkarnain; Fajri, Rahmatul; Dwitya, Yonadiah; Fahril, Muhammad Ari (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2025)
This service aims to improve public information services through the website redesign of the Langsa City Library and Archives Office. The method includes needs analysis, interface design using visual tools, and system implementation based on content management. The results show improvements in visual appearance, navigation, and information access. The redesigned website is more user-friendly, responsive, and helps the public access services online. This redesign has proven effective in enhancing the quality of digital library services.